Cooperative Integrated Reading and Composition for Elementary Reading Comprehension: A Systematic Literature Review - Jessica Rahmadita; Berta Apriza; Yasinta Mahendra (Universitas Pendidikan Ganesha, 2026)
Elementary students’ reading comprehension remains a persistent literacy problem because many learners can read texts but struggle to identify main ideas, interpret information, draw conclusions, and summarize content. This study aims to analyze the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving elementary school students’ reading comprehension through a systematic literature review. Reading comprehension is a fundamental literacy skill that supports students’ ability to understand subject matter, process information, and participate actively in learning. This study reviewed articles published from 2019 to 2023 using Google Scholar as the database. The search used the keywords “CIRC learning model,” “improve the ability,” “reading comprehension of students,” and “elementary school.” Article selection was conducted through screening of titles, abstracts, full texts, citation relevance, and accessibility. Ten articles met the inclusion criteria and were analyzed using descriptive and thematic synthesis. The findings show that CIRC consistently improves reading comprehension by integrating reading, discussion, writing, peer collaboration, and teacher facilitation. Students became more active in understanding texts, exchanging ideas, answering questions, identifying main ideas, and summarizing reading content. Successful implementation requires teacher readiness, suitable reading materials, effective group management, and adequate learning time. This study concludes that CIRC is a relevant cooperative learning model for strengthening elementary reading instruction.